Steady-State-Diagram for Cirulating Fluidized Beds - Wirth, Karl-Ernst (Preprints "International Symposium in Coal Combustion", 1987)
This special issue contains a select 19 of 121 papers presented at the 8th International Symposium on Coal Combustion (ISCC-8), which was held at the Beijing Convention Center on 19−22 July 2015. The first ISCC was inaugurated at Tsinghua University, Beijing, China in 1987 under the consistent support of many distinguished scholars including Prof. Junkai Feng, Prof. Xuchang Xu, Prof. Douglas Smoot, Prof. Adel Sarofim, Prof. Klaus Hein, Prof. Ulrich Renz, Prof. Lothar Reh, Prof. Masayosh Sadakata, Prof. Keiji Makino, and Prof. Jianxiong Mao, etc. Since then, the ISCC has been proudly hosted by Tsinghua University for almost three decades, once every four years, as a non-profit platform to promote Research and Development in the field of science and technology of coal combustion, gasification, and the controls of pollutants and CO2 emissions. The most recent ISCC-8 attracted over 200 engineers and scientists from 14 countries including China, USA, Germany, Japan, UK, Canada, Russia, Australia, Korea, India, Sweden, Poland, Portugal, and Estonia. It was chaired by Prof. Guangxi Yue of Tsinghua University, along with the renewed international advisory committee consisting of 52 leading combustion scholars and experts from 14 countries. For the first time, the ISCC adopted the colloquium chair system to guarantee the quality of the conference papers. After two rounds of peer reviews, 196 technical papers including 5 keynotes, 121 oral presentations and 70 posters were selected, covering six main colloquium topics: <dl class="listitem" id="list_l0005"> – Basic Coal Quality & Combustion – Pulverized Coal Combustion – Fluidized Bed Combustion – Special for CO2 Issues-CCS – Emission Characteristics and Controls – Industrial Application & Coal Utilization. </dl> Among them, 19 papers were chosen for this special issue on FUEL, and other 99 technical papers of high quality were recommended and collected into the Proceedings of the 8th ISCC, to be published by Springer-Tsinghua University Press. The Symposium has once again obtained the vigorous support from the industry as well. International experts from the American Institute of Electrical Engineers, the All-Russian Thermal Engineering Institute and Japanese Coal Company were all present. Domestic experts from the top three power equipment manufacturers, i.e., Harbin Boiler Company Limited, DongFang Boiler Group Co., Ltd. and Shanghai Electric Group, also attended, as well as experts from domestic energy companies like Shenhua, Guodian, and Huaneng groups, thus well representing the global industrial application of clean coal technology. The symposium has strongly reinforced the collaboration and discussion between academic researchers and industry experts, which emphasizes the main theme of the ISCC of establishing an effective bridge between academia and industry. We, all Guest Editors, would like to owe our sincere thanks to FUEL principal editor Prof. John Patrick, and the editorial board of FUEL for giving us the opportunity to publish this special issue of the ISCC-8. We also acknowledge the local organizing committee of the ISCC-8 for organizing a successful symposium, providing passionate services and for recommending these excellent papers. Finally, we thank all the authors and the referees for their contributions in making this issue fruitful and successful.
UnivIS-Import:2015-04-16:Pub.1987.tech.ITC.mechve.steady_73
Keywords: combustion; coal; fluidized; bed